A NOTE ON QUASI SPLIT NULL POINT FEASIBILITY PROBLEMS - Moudafi, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
Inspired by the very recent work by M.-A. Noor and Kh.-I Noor [9] and given a closed convex set-valued mapping $C$, we propose a split algorithm for solving the problem of finding an element $x^*$ in $C(x^*)$ such that its image, $Ax^*$, under a linear operator, $A$, is a zero of a given maximal monotone operator $T$ in Hilbert spaces setting. Then, we present a strong convergence result and state some examples as applications.